Massed Prolonged Exposure for PTSD in Two Firefighters: Preliminary Case Study Findings. Issue 3 (May 2022) - Zwetzig, Sarah E.; Koch, Lauren M.; Blount, Tabatha H.; Graham, Melissa M.; Peterson, Alan L.
Military service members and first responders experience significant trauma exposure in the line of duty. Service members who transition to first-responder positions may be at an increased risk for developing PTSD due to the cumulative effects of trauma exposure. A common criticism of the standard delivery methods for most evidence-based treatments for PTSD is high dropout rates. Massed-prolonged exposure (Massed-PE) has been demonstrated to be efficacious and reduces dropouts by about 50%. This case study is the first of its kind to specifically assess the clinical utility of using Massed-PE to treat PTSD in two firefighters. Results from this case study indicate that both firefighters had significant reductions in their PTSD symptoms. Massed-PE may be an effective approach to treating PTSD in firefighters and may help overcome some of the barriers of conventional treatment delivery. Additional controlled research is needed to further evaluate this promising treatment approach in firefighter populations.